2011
DOI: 10.1007/s00405-011-1747-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of prelaryngeal node metastases on early glottic cancer treatment results

Abstract: The aim of the study was to examine the impact of positive prelaryngeal node on the outcome of early glottic cancer and to compare the rate of local and regional recurrences and overall survival rates in patients with positive and negative Delphian node (DN). In the years 1989-2008, a consecutive cohort of 212 patients with T1b and T2 glottic cancer with anterior commisure involvement were treated by means of supracricoid partial reconstructive laryngectomies. No adjuvant radiotherapy was administered. Out of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Usually, the DLN includes one to four lymph nodes and receives lymphatic drainage from the larynx and all areas of the thyroid [12]. Previous literature has reported that DLN positivity is a measurable parameter to predict extensive lymph node metastasis, recurrence and poor overall survival in laryngeal and hypopharyngeal cancer [25,26]. However, there is insu cient published data to support the thesis that metastasis to the DLNs is associated with outcome in thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, the DLN includes one to four lymph nodes and receives lymphatic drainage from the larynx and all areas of the thyroid [12]. Previous literature has reported that DLN positivity is a measurable parameter to predict extensive lymph node metastasis, recurrence and poor overall survival in laryngeal and hypopharyngeal cancer [25,26]. However, there is insu cient published data to support the thesis that metastasis to the DLNs is associated with outcome in thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The DLN receives afferent lymph ow from the larynx and thyroid gland, which then ows towards the central and lateral neck lymph nodes [12]. Undoubtedly, DLN is an independent risk factor for predicting widespread lymph node metastasis and increased recurrence in laryngeal carcinoma [25,26]. Whether DLN metastasis is a risk factor for PTC has rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Nakayama, Wierzbicka and Isaacs reported the incidence of lymph nodes, also known as Delphian lymph nodes, as 41%, 13% and 26%, respectively (Isaacs et al, ; Nakayama et al, ; Wierzbicka et al, ). We observed lymph nodes in nine of our 30 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports show the involvement of the DLN in head-neck malignancies. These reports suggest that these lymph nodes are important during surgery and for the prognosis of thyroid, laryngeal, and glottis tumours [ 3 6 ].…”
Section: Introductionmentioning
confidence: 99%